A Ketone Ester Drink Enhances Endurance Exercise Performance in Parkinson’s Disease - Norwitz, Nicholas G.; Dearlove, David J.; Lu, Meng; Clarke, Kieran; Dawes, Helen; Hu, Michele T. (Frontiers in Neuroscience, 2020)
Objectives: Routine exercise is thought to be among the only disease-modifying treatments for Parkinson’s disease; however, patients’ progressive loss of physical ability limits its application. Therefore, we sought to investigate whether a ketone ester drink, which has previously been shown to enhance endurance exercise performance in elite athletes, could also improve performance in persons with Parkinson’s disease. Participants: 14 patients, aged 40-80 years, with Hoehn and Yahr stage 1-2 Parkinson’s disease. Intervention: A randomized, placebo-controlled, crossover study in which each participant was administered a ketone ester drink or an isocaloric carbohydrate-based control drink on separate occasions prior to engaging in a steady state cycling test at 80 rpm to assess endurance exercise performance. Outcomes Measures: The primary outcome variable was length of time participants could sustain a therapeutic 80 rpm cadence. Secondary, metabolic outcomes measures included cardiorespiratory parameters as well as serum -hydroxybutyrate, glucose, and lactate. Results: The ketone ester increased the time that participants were able to sustain an 80 rpm cycling cadence by 24% ± 9% (p = 0.027). Correspondingly, the ketone ester increased b-hydroxybutyrate levels to >3 mmol/L and decreased respiratory exchange ratio, consistent with a shift away from carbohydrate-dependent metabolism. Conclusion: Ketone ester supplementation improved endurance exercise performance in persons with Parkinson’s disease and may, therefore, be useful as an adjunctive therapy to enhance the effectiveness of exercise treatment for Parkinson’s disease.